Editorial: Five Years of Growth: A New Era for Contemporary Pediatric Dentistry - Burak Buldur (Contemporary Pediatric Dentistry, 2025)
It is with great pride that we introduce the first issue of Contemporary Pediatric Dentistry (CPD) for 2025. Since its establishment, CPD has served as an international, open-access, peer-reviewed journal dedicated to advancing the science and clinical practice of pediatric dentistry.